Prognostic Significance of Macrophage Phenotypes in Peri-Tumoral Normal Tissue of Early-Stage Breast Cancer - Hirschmann, Marcel; Schnellhardt, Sören; Rübner, Matthias; Segelhorst, Sarah; Ott, Oliver; Erber, Ramona; Daniel, Christoph; Büttner-Herold, Maike; Gaß, Paul; Fietkau, Rainer; Distel, Luitpold (Cells, 2025)
In recent years, tumor-infiltrating inflammatory cells within the tumor microenvironment have been extensively studied. However, much less is known about inflammatory cells in the normal tissue surrounding tumors. In this study, we assess the prognostic significance of tumor-associated macrophages (TAMs) in relation to disease-free survival (DFS) in patients with early-stage breast cancer. Our cohorts included patients from the APBI and BBCC trials, with eligible tumors being small in size and showing no signs of metastasis. We analyzed eight distinct inflammatory cell types in the normal tissue surrounding tumors, with a particular focus on the various macrophage subsets. There were clear differences in the frequencies of the different inflammatory cells, with a higher abundance of cells being found in the intraepithelial compartment compared to the stromal compartment. Notably, we found that M2-type macrophages located in the stromal compartment of tumor distant normal tissue exhibited a positive prognostic impact, in contrast to the M2-type macrophages found within the tumor itself. In the normal tissue surrounding tumors, there are surprisingly clear prognostic predictions for DFS. Normal tissue surrounding breast cancer tumors is clearly influenced by the tumor and could also influence the tumor in terms of growth and metastasis. Tumor-influenced inflammatory cells in the surrounding normal tissue could prevent the immune system from acting against the tumor and promote tumor growth through inflammation.
CRIS-Team Scopus Importer:2025-06-20
Keywords: early-stage breast cancer; M1; M2; macrophages; microenvironment; normal tissue; partial breast irradiation; radiotherapy; tumor-infiltrating inflammatory cells

Shifts in Macrophage as a prognostic Biomarker in Patients with luminal Breast Cancer - A Confirmatory Study - Schnellhardt, Sören; Segelhorst, Sarah; Erber, Ramona; Daniel, Christoph; Hartmann, Arndt; Fasching, Peter; Beckmann, Matthias; Fietkau, Rainer; Distel, Luitpold; Rübner, Matthias (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16